Tingkat Kepuasan Pengguna Layanan Unit TIK Universitas Tidar Studi pada Fakultas Isipol - Arsanti, Syavira Azzahra; Augista, Gardenia; Agustian, Kevin Bariklana; Nuramalia, Arifah Ramadhani; A’yun, Nathaniaura Heysa Qurrota; Nugraha, Joko Tri (ANTASENA: Governance and Innovation Journal, 2025)
Rapid developments in information technology require universities to continuously improve the quality of their digital services to support academic and administrative activities. The Information and Communication Technology (ICT) Unit plays an important role in ensuring the availability of efficient, responsive, and needs-oriented technology services for the academic community. User satisfaction levels are influenced by the quality of available facilities and the level of academic services provided. This study aims to evaluate user satisfaction with the services of the Information and Communication Technology (ICT) Unit at Tidar University, particularly in the Faculty of Social and Political Sciences. The method used is descriptive quantitative, involving 50 respondents consisting of lecturers, staff, and students. Data collection was conducted through a questionnaire based on SERVQUAL indicators covering five aspects: tangibles, reliability, responsiveness, assurance, and empathy. The findings of this study indicate that most respondents are satisfied with the quality of services provided by the ICT Unit, especially in terms of tangibles and assurance. However, improvements in responsiveness and empathy are still needed to strengthen the overall quality of services. The reliability index of the measuring instrument (Cronbach's Alpha = 0.946) shows a very good level of internal consistency, which indicates the reliability of the instrument involved. Elements such as the neatness of physical facilities, the professional attitude of staff, and punctuality in providing services are the most significant factors affecting user satisfaction. This study emphasizes the importance of improving the quality of digital services in higher education as part of an information technology-based academic transformation strategy.